Examination of Common Coronavirus Antibodies in SARS-CoV-2-Infected and Uninfected Participants in a Household Transmission Investigation. (20th July 2022) - Stumpf, Megan M; Freeman, Brandi; Mills, Lisa; Lester, Sandra; Chu, Victoria T; Kirking, Hannah L; Thornburg, Natalie J; Killerby, Marie E
Abstract: We compared paired serum specimens from household contacts of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cases with detectable SARS-CoV-2 seroconversion with contacts who remained seronegative. No protection from SARS-CoV-2 infection was associated with human coronavirus antibodies; however, an increase in common betacoronavirus antibodies was associated with seroconversion to SARS-CoV-2 in mild to moderately ill cases.